Sonography of the ankle: The lateral ankle and ankle sprains. Issue 4 (28th September 2017) - McKiernan, Sharmaine; Fenech, Michelle; Fox, Deborah; Stewart, Ian
Abstract: Ankle sprains can be considered a relatively common injury particularly from sports injuries. While a sprain is generally a benign injury, symptoms can persist and lead to long‐term disability and instability. This article includes an overview of the lateral ankle including ligament and tendon anatomy, scanning technique and information on the common sprains the sonographer may encounter. It is important that sonographers are familiar with the lateral ankle anatomy and potential injuries and how complicated an ankle sprain can be.